Case Report: A Case of COVID Vaccine-Induced Thrombotic Thrombocytopenia Manifested as Pulmonary Embolism and Hemorrhagia. A First Reported Case From Slovakia - Ihnatko, Martin; Truchla, Ivana; Ihnatková, L'udmila; Prohászka, Zoltán; Lazúrová, Ivica (Frontiers in Medicine, 2022)
COVID-19 vaccine-induced thrombotic thrombocytopenia (VITT) is a rare complication of adenoviral vector (ChAdOx1 nCoV-19) vaccine administration. It is presented as thrombocytopenia and thrombotic manifestations in various sites, especially in cerebral veins. Pulmonary emboli have been reported rarely. We present a case of the young male patient who developed severe thrombocytopenia and pulmonary embolism 12 days after first dose of vaccine. Severe thrombocytopenia, skin haematomas and segmental pulmonary emboli were detected. Anti platelet factor 4 (aPF-4) antibody was highly positive supporting the diagnosis of VITT. Prompt treatment with fondaparinux, intravenous immunoglobulin and prednisone lead to a marked improvement of clinical condition and thrombocytes count. We report probably the first known case of VITT in Slovakia.